2015
DOI: 10.1158/2159-8290.cd-14-0863
|View full text |Cite
|
Sign up to set email alerts
|

The Vigorous Immune Microenvironment of Microsatellite Instable Colon Cancer Is Balanced by Multiple Counter-Inhibitory Checkpoints

Abstract: We examined the immune microenvironment of primary colorectal cancer (CRC) using immunohistochemistry, laser capture microdissection/qRT-PCR, flow cytometry and functional analysis of tumor infiltrating lymphocytes. A subset of CRC displayed high infiltration with activated CD8+ CTL as well as activated Th1 cells characterized by IFN-γ production and the Th1 transcription factor Tbet. Parallel analysis of tumor genotypes revealed that virtually all of the tumors with this active Th1/CTL microenvironment had de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

52
988
3
20

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,225 publications
(1,107 citation statements)
references
References 27 publications
52
988
3
20
Order By: Relevance
“…The observed differences between MMR-proficient LM-CRC and MMR-proficient primary CRC are to some extent reminiscent of those found between MMR-deficient primary CRC and MMR-proficient primary CRC by Llosa et al. 31 They demonstrated that MMR-deficient primary CRC displayed higher infiltration with CD8 + CTL as well as upregulated expression of PD-1, PD-L1, CTLA4 and LAG3 compared to MMR-proficient primary CRC, and suggested that these differences contributed to the enhanced clinical responsiveness to anti-PD-1 therapy of microsatellite instable CRC compared with microsatellite stable CRC. 31 In addition, we found that LM-CRC contained increased frequencies of professional APC subsets (mDC and monocytes) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed differences between MMR-proficient LM-CRC and MMR-proficient primary CRC are to some extent reminiscent of those found between MMR-deficient primary CRC and MMR-proficient primary CRC by Llosa et al. 31 They demonstrated that MMR-deficient primary CRC displayed higher infiltration with CD8 + CTL as well as upregulated expression of PD-1, PD-L1, CTLA4 and LAG3 compared to MMR-proficient primary CRC, and suggested that these differences contributed to the enhanced clinical responsiveness to anti-PD-1 therapy of microsatellite instable CRC compared with microsatellite stable CRC. 31 In addition, we found that LM-CRC contained increased frequencies of professional APC subsets (mDC and monocytes) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…31 They demonstrated that MMR-deficient primary CRC displayed higher infiltration with CD8 + CTL as well as upregulated expression of PD-1, PD-L1, CTLA4 and LAG3 compared to MMR-proficient primary CRC, and suggested that these differences contributed to the enhanced clinical responsiveness to anti-PD-1 therapy of microsatellite instable CRC compared with microsatellite stable CRC. 31 In addition, we found that LM-CRC contained increased frequencies of professional APC subsets (mDC and monocytes) (Fig. 1C), which may result in improved presentation of tumor antigens to intra-tumoral T cells as well as more PD-L1 and MHC-II expression in LM-CRC compared with primary CRC, because in LM-CRC mDC and monocytes expressed more PD-L1 and MHC-II than B cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune evasive mechanisms include loss of the MHC class I subunit B2M and up-regulation of the T-cell inhibitor PD-L1. 13,14 Differences in mechanisms, e.g. related to deregulation of MHC class I expression, apply between sporadic and hereditary MSI tumors, and motivate mechanistic explanation related to the variable response rates observed in sporadic and Lynch syndrome-associated MSI tumors treated with anti-PD-1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 This anti-tumorigenic effect may be counter-balanced by immune-evasive mechanisms, such as loss of the MHC class I subunit, beta-2-microglobulin (B2M) and up-regulation of the T-cell inhibitor programmed death 1 ligand 1 (PD-L1). 13,14 B2M loss has been associated with loss of MHC class I receptors suggesting that this subset may not elicit neoepitope-induced T cell responses. 4,15 In contrast, high levels of PD-L1 have been associated with T cell exhaustion that can be reversed by inhibition of the programmed death 1 (PD-1)/PD-L1 binding.…”
Section: Introductionmentioning
confidence: 99%